A EDUCAÇÃO AMBIENTAL COMO ESTRATÉGIA DE MOBILIZAÇÃO SOCIAL PARA O ENFRENTAMENTO DA EROSÃO NO MUNICÍPIO DE IVINHEMA/MS - MACIEL JOAO, Danielle; ITIHARA, Gabriela Missae; ZUCCHINI, Lilian Giacomini Cruz; MORAIS, Glaucia Almeida (ANAIS DO ENIC, 2020)
-